Comparing the cost-effectiveness of water conservation policies in a depleting aquifer: a dynamic analysis of the Kansas High Plains - Ding, Ya; Peterson, Jeffrey M. (My University, 2012)
This research analyzes two groundwater conservation policies in the Kansas High Plains located within the Ogallala aquifer: 1) cost-share assistance to increase irrigation efficiency; and 2) incentive payments to convert irrigated crop production to dryland crop production. To compare the cost-effectiveness of these two policies, a dynamic model simulated a representative irrigator’s optimal technology choice, crop selection, and irrigation water use over time. The results suggest that the overall water-saving effectiveness can be improved when different policy tools are considered under different conditions. High prevailing crop prices greatly reduce irrigators’ incentive to give up irrigation and therefore cause low enrollment and ineffectiveness of the incentive payment program. In areas with low aquifer-saturated thickness, the incentive payment program is more effective, whereas in areas with relatively higher water availability, the cost-share program could be a better choice.
Keywords: Cost-share program; Incentive payments; Ogallala aquifer; Dynamic optimization; Groundwater conservation